Health‐care professionals' experiences of patient participation among older patients in intermediate care-At the intersection between profession, market and bureaucracy - Linda Aimée Hartford Kvæl; Jonas Debesay; Asta Bye; Astrid Bergland (Wiley, 2019)
Abstract Background Patient participation is a key concern in health care. Nevertheless, older patients often do not feel involved in their rehabilitation process. Research states that when organizational conditions exert pressure on the work situation, care as a mere technical activity seems to be prioritized by the health‐care staff, at the expense of patient involvement. Objective The aim of this article is to explore how health‐care professionals experience patient participation in IC services, and explain how they perform their clinical work balancing between the patient's needs, available resources and regulatory constraints. Design Using a framework of professional work and institutional logics, underpinned by critical realism, we conducted semi‐structured interviews with 18 health‐care professionals from three IC institutions. Results IC appears as an important service in the patient pathway for older people with a great potential for patient participation. However, health care staff may experience constraints that prohibit them from using professional discretion, which is perceived as a threat to patient participation. Further, they may adopt routines that simplify their interactions with patients. Our results call for more emphasis on an individualized rehabilitation process and a recognition that psychological and social aspects are critical for patient participation in IC. Conclusion Patients interact in the face of conflicting institutional priorities or protocols. The study adds important knowledge about the practice of patient participation in IC from a front‐line provider perspective. Underlying mechanisms are identified to understand and recommend how to facilitate patient participation at different levels in narrowing the gap between policy and clinical work in IC.